2020
DOI: 10.3390/polym12020340
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Chemical and Structural Composition of Lignocellulosic Biomasses in Tetraploid Rice Straw

Abstract: The improvement of the saccharification of rice straw is one of the strategies to reduce the sophisticated pretreatment that results in high cost and is unfriendly to the environment. We explored the cell wall features in tetraploid rice and highlighted the enhanced saccharification of tetraploid with large biomass. Results showed that lignin content and S/G ratio reduced to 17.09% and 0.37, respectively, in tetraploid straw by the determination of the pyGC-MS method. After the pretreatment, the cellulose crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Compared with Arabidopsis diploids, the lignin contents of tetraploids, hexaploids, and octaploids were decreased by 20%, 50%, and 55%, respectively [14]. A similar phenomenon was found for polyploid crops such as rice and potatoes; the lignin content of polyploids was significantly lower than that of diploids [15,16].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Compared with Arabidopsis diploids, the lignin contents of tetraploids, hexaploids, and octaploids were decreased by 20%, 50%, and 55%, respectively [14]. A similar phenomenon was found for polyploid crops such as rice and potatoes; the lignin content of polyploids was significantly lower than that of diploids [15,16].…”
Section: Introductionsupporting
confidence: 67%
“…From the results of our study, we suppose that polyploids have larger cells, usually accompanied by decreased cell-surface areas per unit volume, which possibly decrease the demand for lignin accumulation. Lignin content is usually reduced in multiple polyploid plants, such as poplar in this study, shrub willow, Arabidopsis, rice, and potato [12][13][14][15][16]. In contrast, the cellulose and hemicellulose contents of polyploids showed different trends in different species.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although lot of work has been done on crop improvement for high biomass yield, improving the pretreatment process and using biotechnological methods to increase the saccharification capacity could also improve straw utilization (Tian et al, 2018 ). Existing studies have shown that many crops have unique biomass composition, but knowledge about difference in biomass composition between high-cultivated varieties derived from same parents is either lacking or only superficial (Chen et al, 2020 ; Samavi and Rakshit, 2020 ). For example, rice varieties cultivated in different regions of the world might have different straw cell wall composition, so application of one pretreatment technology for straw conversion to bioethanol is undesirable (Gao et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…So many factors of the cell wall structures might affect pretreatment effect (Li et al, 2010 ; Zhang et al, 2011 ). For example, crystalline cellulose is not easily decomposed, and lignin and hemicellulose affect the accessibility of enzymes (Lenting and Warmoeskerken, 2001 ; Van Wyk, 2001 ; Qian et al, 2005 ; Brandt et al, 2013 ; Chen et al, 2020 ). Various pretreatment methods are available, including chemical biological and physical methods.…”
Section: Introductionmentioning
confidence: 99%